Inviscid quasi-neutral limit of a Navier-Stokes-Poisson-Korteweg system - Wang, Hongli; Yang, Jianwei (Mathematical Modelling and Analysis, 2018)
The combined quasi-neutral and inviscid limit of the Navier-Stokes-Poisson-Korteweg system with density-dependent viscosity and cold pressure in the torus T3 is studied. It is shown that, for the well-prepared initial data, the global weak solution of the Navier-Stokes-Poisson-Korteweg system converges strongly to the strong solution of the incompressible Euler equations when the Debye length and the viscosity coeﬃcient go to zero simultaneously. Furthermore, the rate of convergence is also obtained.